Pojok Baca: Optimalisasi Minat Baca Santri di Pondok Pesantren MAS Tarbiyah Islamiyyah Candung - Miftahul Husna; Sumetri Sumetri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract Students' interest in reading is still low due to a lack of literacy awareness, the lack of quality books and the high use of gadgets that distract from reading. The reading corner programme was implemented to create an interactive reading corner, but its implementation is still experiencing obstacles. The purpose of this study is to analyse the optimisation of interest in reading through the reading corner program at MAS TI Candung Islamic boarding school, by identifying obstacles and constraints and assessing the impact of the program on increasing students' interest in reading. This was done by analysing the implementation of the reading corner program at the MAS TI Candung boarding school to find out the supporting and inhibiting factors and the impact on increasing students' interest in reading. The research method used was descriptive qualitative research with the research subjects being two students of MAS TI Candung boarding school, one library staff and one homeroom teacher. Data collection techniques were conducted through field observations and individual interviews. The results showed that the reading corner programme at MAS TI Candung has been running supported by various factors such as stakeholder participation and the availability of human resources. The main inhibiting factors are book limitations and implementation time. The impact of the implementation of this programme includes an increase in students' interest in reading and literacy skills. It is concluded that the reading corner program is effective in optimising students' interest in reading. AbstrakMinat baca pelajar masih rendah disebabkan kurangnya kesadaran literasi, minimnya buku bermutu, dan tingginya penggunaan gadget yang mengalihkan perhatian dari membaca. Program pojok baca diterapkan untuk menciptakan sudut baca interaktif, namun implementasinya masih mengalami kendala. Tujuan dari penelitian ini adalah untuk menganalisis optimalisasi minat baca melalui program pojok baca di pondok pesantren MAS TI Candung, dengan cara mengidentifikasi hambatan dan kendala serta menilai dampak program terhadap peningkatan minat baca santri. Hal ini dilakukan dengan menganalisis pelaksanaan program pojok baca di pondok pesantren MAS TI Candung guna mengetahui faktor pendukung dan penghambat serta dampaknya terhadap peningkatan minat baca santri. Metode penelitian yang digunakan adalah penelitian kualitatif deskriptif dengan subjek penelitian dua santri pondok pesantren MAS TI Candung, satu staff perpustakaan dan satu wali kelas. Teknik pengumpulan data dilakukan melalui observasi lapangan dan wawancara individual. Hasil penelitian menunjukkan bahwa program pojok baca di MAS TI Candung telah berjalan dengan didukung oleh berbagai faktor seperti peran serta stakeholder dan ketersediaan sumber daya manusia. Adapun faktor penghambat utama adalah keterbatasan buku dan waktu pelaksanaan. Dampak dari penerapan program ini antara lain peningkatan minat baca dan kemampuan literasi siswa. Disimpulkan bahwa program pojok baca efektif dalam upaya optimalisasi minat baca santri.